Possibilities for reducing fungicide treatments in sour cherry production - Borovinova, Maria (Acta Agraria Debreceniensis, 2008)
The aim of this study was to investigate the possibilities for reducing fungicide treatments of sour cherry. The study was conducted in fruit bearing sour cherry orchards of the Institute of Agriculture at Kyustendil during 1991-2005. Cherry leaf spot was controlled by postinfection applications of ergosterol biosynthesis inhibitors and dodine. Bacterial canker, brown rot, shot-hole syndrome were controlled by protective treatments with copper-containing fungicides in late autumn and early spring. Insecticide treatments were applied when it was necessary. Blumeriella jaapii is the main pathogen of sour cherry which can be controlled successfully by postinfection treatments. Their number could be reduced in some years. Sprays against leaf spot were effective against other diseases too. Protective treatments against Pseudomonas syringae with copper-containing fungicides were effective against shot-hole syndrome and Monilinia laxa as well as Monilinia fructigena.